Knowledge of HIV and intention to engage in risky sexual behaviour and practices among senior school adolescents in Ibadan, Nigeria (2018)
A high proportion of adolescents still engage in risky sexual behaviours that put them at risk of infection complications of risky sexual behaviours including Human Immunodeficiency Virus (HIV) infection despite the different interventions already in place. This study was designed to determine the adolescents’ knowledge of HIV, intention to engage in risky sexual behaviour and sexual practices. A 3-stage sampling technique was used to select 240 adolescents in senior secondary schools in Ibadan, Nigeria. Data were obtained using a pretested, semi-structured, self-administered questionnaire. Data were analysed using descriptive statistics and Chi-square test at 5% level of significance. The mean age of the respondents was 16.3±1.4 years and 126(52.5%) were females. Only 34.3% had good knowledge of HIV and there were misconceptions about its transmission. Most of the respondents (95.0%) had intention to engage in risky sexual behaviour and those with good knowledge of HIV were willing to engage in risky sexual behavour with familiar people. Good knowledge was associated with intention to engage in low-risk sexual behaviour. Seventy-nine (32.9%) were sexually active and they had better knowledge of HIV. Knowledge of HIV was low among this study group and was not associated with their intention to engage in risky sexual behaviour. There is need for more effective and appropriate school and community-based intervention programmes which can impact positively on the adolescents’ sexual behaviour.